Quick response in the flows of a modern city - Kozlova , Yulia; Zolotarev, Maxim (project baikal, 2025)
The modern city, in the unity of its material and iconic objects, is a multi-level text system that includes individual and collective symbolic elements, as well as means of mastering the experience of interacting with the urban text. This article provides a justification for the role of algorithmic means (Quick Response or QR) in understanding urban space. A QR code is considered as a graphic object that connects objects of the architectural and landscape layer of an urban text with communicative flows and social structures. The virtual space contains specific sign complexes, the interaction with which allows you to solve cognitive and practical tasks, communicate, and perform chains of social actions.
Keywords: multitextual city; urban flows; persistent uncertainty; transstructural discourse; technological transition; QR code